Differentially Substituted Phenylene-Containing Oligoacene Derivatives - Luppino, Sarah P.; Swager, Timothy M. (Synlett, 2017)
We report the synthesis and characterization of seven new linearly conjugated ladder compounds of the phenylene-containing oligoacene molecule class. Each derivative incorporates a fused four-membered-ring linkage in the acene-like backbone. Crystal packing, spectroscopic and electrochemical properties of the molecules are described.
Keywords: phenylene-containing oligoacenes; conjugated ladder molecules; Diels–Alder reaction; acenes; [N]phenylenes